The effect of nitrogen fertigation and harvesting time on plant growth and chemical composition of centaurea raphanina subsp. mixta (DC.) Runemark - Petropoulos, Spyridon Α. (2018)
The aim of the present study was to evaluate the effect of nitrogen fertigation (0, 200, 400, and 600 ppm of total nitrogen) and harvesting time (9 March 2018 and 19 April 2018) on the plant growth, chemical composition, and bioactive properties of Centaurea raphanina subsp. mixta plants. The highest yield of fresh leaves was observed for the treatment of 200 ppm of N without compromising nutritional value. The increasing nitrogen levels resulted in an increase of a- and total tocopherols and sugars content, especially in the second harvest for tocopherols and in the first harvest for sugars. Similarly, total organic acids and oxalic acid content increased with increasing nitrogen levels in both harvests, while fatty acids composition had a varied response to the tested factors. Pinocembrin neohesperidoside and pinocembrin acetyl neohesperidoside isomer II were the most abundant phenolic compounds with the highest content being observed in the control treatment of the first and second harvest, respectively. The highest antioxidant activity was observed for the control and the 600 ppm treatments of the second harvest for the OxHLIA and TBARS assays, respectively, probably due to the high content of pinocembrin acetyl neohesperidoside isomer II and a-tocopherol, respectively. Finally, cytotoxic effects and antimicrobial properties showed a varied response depending on the treatment. In conclusion, C. raphanina subsp. mixta has low requirements of nitrogen to achieve the highest yield, while a varied response to the tested fertigation treatments and harvesting time was observed in terms of the chemical composition and the bioactive properties.